Peranan Kebijakan Pimpinan Terhadap Kenyamanan Peserta Didik Di Pondok Pesantren Tafrijul Ahkam Cikiray Kecamatan Cibadak Kabupaten Lebak Tahun Pelajaran 2015 - Ujang Saefudin Rosyid (E-Jurnal Aksioma Ad-Diniyyah : The Indonesian Journal of Islamic Studies, 2015)
An organization will succeed or even fail, mostly determined by a leader. A noble expression that says that leaders are responsible for failure to carry out a job, is an expression that occupies the position of leader in an organization in the most important position. The purpose of this study is to obtain data on the role of the leadership, to know the convenience of students and to know the role of the Leadership Policy on the Comfort of students at the Tafrijul Ahkam Cikiray Islamic Boarding School in Cibadak District, Lebak Regency 2015/2016 Academic Year. The method used in this study is analytical description. This method is used because in the study only collects data only, then the data is processed up to drawing conclusions. This study is a study that uses an approach through a qualitative approach. Qualitative approach is the research of data collected not in the form of the numbers, but come from interview texts, field notes, personal documents, memo notes, and other official documents. The results of the study of the role of leaders in the Tafrijul Ahkam Cikiray Islamic Boarding School in Rangkasbitung District, Lebak Regency 2015/2016 Academic Year greatly influenced the teaching and learning conditions, this was proven by the leadership paying attention to the school / class physical conditions, socio-emotional settings and organizational arrangements and administrative arrangements in the school environment and in the classroom environment. The comfort of students at the Tafrijul Ahkam Cikiray Islamic Boarding School in Rangkasbitung District, Lebak Regency 2015/2016 Academic Year can be said to be comfortable because the physical condition and location of Islamic boarding schools meet the standards. Leadership Policy on the Comfort of Students at Tafrijul Islamic Boarding School 2015/2016 lessons. The role of the leader in determining policies to improve the comfort of students, should know and choose effective ways. This knowledge and skills are needed, because choosing effective ways of increasing comfort will enable teachers and students to be able to apply and determine ways that are appropriate to individual, psychological and individual student needs. Suatu organisasi akan berhasil atau bahkan gagal sebagian besar di tentukan oleh seorang pemimpin. Suatu ungkapan mulia yang mengatakan bahwa pemimpinlah yang bertanggung jawab atas kegagalan pelaksanaan suatu pekerjaan, merupakan ungkapan yang mendudukan posisi pemimpin dalam suatu organisasi pada posisi yang terpenting. Tujuan penelitian ini adalah Untuk memperoleh data peranan pimpinan, mengetahui kenyamanan peserta didik dan mengetahui peranan Kebijakan Pimpinan  terhadap Kenyamanan peserta didik di Pondok Pesantren Tafrijul Ahkam Cikiray Kecamatan Cibadak Kabupaten Lebak Tahun Pelajaran 2015/2016. Metode yang digunakan dalam penelitian ini adalah deskriftip analitis.Metode ini digunakan karena dalam penelitian hanya mengumpulkan data semata yang selanjutnya data tersebut diolah sampai dengan penarikan kesimpulan.Penelitian ini merupakan penelitian yang menggunakan pendekatan melalui pendekatan kualitatif.pendekatan kualitatif adalah penelitian data yang dikumpulkan bukan berupa angka-angka, melainkan berasal dari naskah wawancara, catatan lapangan, dokumen pribadi, catatan memo, dan dokumen resmi lainnya.Hasil penelitian Peranan pimpinan di Pondok Pesantren Tafrijul Ahkam Cikiray Kecamatan Rangkasbitung Kabupaten Lebak Tahun Pelajaran 2015/2016 sangat mempengaruhi terjadinya kondisi belajar-mengajar, hal ini terbukti pimpinan memperhatikan pengaturan kondisi fisik sekolah/kelas, pengaaturan sosio-emosional, dan pengaturan organisasional serta pengaturan administrasi di lingkungan sekolah maupun di lingkungan kelas. Kenyamanan peserta didik di Pondok Pesantren Tafrijul Ahkam Cikiray Kecamatan Rangkasbitung Kabupaten Lebak Tahun Pelajaran 2015/2016 sudah bisa dikatakan nyaman karena kondisi fisik dan lokasi pondok pesantren sudah memenuhi standar.Kebijakan Pimpinan  terhadap Kenyamanan peserta didik di Pondok Pesantren Tafrijul Ahkam Cikiray Kecamatan Cibadak Kabupaten Lebak Tahun Pelajaran 2015/2016. Peranan Pemimpin dalam menentukan kebijakan untuk meningkatkan kenyamanan peserta didik, hendaknya mengetahui dan memilih cara yang efektif. Pengetahuan dan keterampilan ini diperlukan, sebab dalam memilih cara meningkatkan kenyamanan yang efektif akan memungkinkan guru dan peserta didik mampu menerapkan dan menentukan cara yang sesuai dengan perbedaan individual, kejiwaan dan kebutuhan setiap siswa.